Analisis Pertumbuhan Dana Pihak Ketiga Dan Pengaruhnya Terhadap Likuiditas - Mertyani Sari Dewi; Ni Made Rianita (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2021)
The purpose of this study was to determine the growth of third party funds and their effect on liquidity in the LPD Desa Pakraman Gerokgak. The population in this study was the monthly balance sheet financial statements at the LPD,while the sampling was carried out using the LPD data sample in the form of balance reports for the last 5 years 2016-2020 period. The results showed that the Growth of Third Party Funds on Liquidity by calculating the growth ratio and the Loan to Deposit Ratio (LDR) ratio. The growth of third party funds has fluctuated on average around 1.39% each month and the Loan to Deposit Ratio (LDR) from 2014 to 2018 has reached a fairly good value from the criteria for assessing bank soundness based on the established liquidity aspects.